The Relationship Between Reactive Oxygen Species and Endothelial Cell Metabolism - Alhayaza, Raid; Haque, Emaan; Karbasiafshar, Catherine; Sellke, Frank W.; Abid, M. Ruhul (Frontiers in Chemistry, 2020)
Cardiovascular disease (CVD) has been the leading cause of death for many decades, highlighting the importance of new research and treatments in the field. The role of hypoxia and subsequent free radical production (reactive oxygen species; ROS) have become an area of particular interest in CVD. Interestingly, our and other labs have recently reported positive roles of subcellular ROS in modulating endothelial cell (EC) metabolism, proliferation and angiogenesis. This bi-directional relationship between ROS and EC metabolism as well as functional changes continues to be an area of active research. Interestingly, ECs have been shown to rely on anaerobic processes for ATP generation, despite their direct access to oxygen. This paradox has proven to be beneficial as the major reliance on glycolysis produces ATP faster, preserves oxygen and results in reduced ROS levels in contrast to oxidative phosphorylation. This review will address the relationship between ROS and carbohydrate, lipid, and nitrogen metabolism in ECs, and their effects on EC phenotype such as sprouting angiogenesis.